Public Art as City Symbol: Legal Challenges in Copyright and Moral Rights Protection - Hendrico Dolok; Hulman Panjaitan; Andrew Betlehn (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Intellectual property protection for public art installations presents a complex legal challenge when such works evolve into recognizable urban icons. This research aims to analyze the legal safeguards provided to creators of public artworks under the framework of Law Number 28 of 2014 and to evaluate the application of the principle of legal certainty in the "Urban Light" copyright dispute. Utilizing a normative legal research methodology with a focus on statutory and case approaches, this study examines the judicial reasoning within Decision No. 31/Pdt.Sus-Hak Cipta/2020/PN.Niaga.Jkt.Pst. The results demonstrate that public artworks are afforded automatic protection through the declarative principle, ensuring that their status as public symbols does not diminish the creator's exclusive moral and economic rights. Furthermore, the findings indicate that the Indonesian judiciary prioritized material truth by applying the "first to create" doctrine, which led to the cancellation of copyright registrations made in bad faith by unauthorized parties. The study concludes that achieving a reconciliation between legal certainty and substantive justice is vital for maintaining the integrity of the creative industry. These findings offer significant implications for the Directorate General of Intellectual Property in enhancing substantive verification protocols for works with established global reputations. Ultimately, this research serves as a crucial legal precedent for the protection of international artistic monuments within national jurisdictions against practices of plagiarism disguised as inspiration.